2009
DOI: 10.1016/j.carbon.2009.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-induced distortion of ions in the pores of carbon electrodes for electrochemical capacitors

Abstract: This paper reports the effect of confining ionic species of the electrolyte inside the porosity of carbon electrodes during the performance of electrochemical capacitors. Solvent-free ionic liquids and a conventional organic medium were used as electrolytes, while two series of carbons with controlled pore sizes -one of them obtained from nanocasting procedure -were used as electrode materials. Our results demonstrate that under the effect of the electric field applied during the polarization of the electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 29 publications
6
48
0
Order By: Relevance
“…As expected from experimental studies 17,18 , the adsorption of ions in confined environments leads to their partial desolvation. This is clearly visible on the distributions of the ACN solvent molecule coordination number around each ion, as shown in Fig.…”
Section: Supercapacitors Simulationssupporting
confidence: 53%
“…As expected from experimental studies 17,18 , the adsorption of ions in confined environments leads to their partial desolvation. This is clearly visible on the distributions of the ACN solvent molecule coordination number around each ion, as shown in Fig.…”
Section: Supercapacitors Simulationssupporting
confidence: 53%
“…In comparison, PAN-derived CNFs showed a broader distribution of micropore size with an average value of 1.4 nm. Therefore, PAN/pitch-derived CNFs are theoretically more suitable as electrode materials in an aqueous medium, because the ultramicropores in the carbon structure match well with the size of solvated ions (less than 1.0 nm) [13].…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, PAN-derived CNFs showed a broader distribution of micropore size with an average value of 1.4 nm. Therefore, PAN/pitch-derived CNFs are theoretically more suitable as electrode materials in an aqueous medium, because the ultramicropores in the carbon structure match well with the size of solvated ions (less than 1.0 nm) [13].STM provides information on the domain size and micro-structure of the domains of CNFs. As the pitch concentration increased, the shape of the surface changed from small particle-like to flat plate-like to large particle-like (Fig.…”
mentioning
confidence: 99%
“…26 Note that the present calorimeter was configured for two electrode configuration and could not provide the potential evolution across each electrode separately. However, Ania et al 69 showed that, at low cell potential (i.e., ψ s ≤ 1 V), the potential difference was identical across the positive and negative electrodes of a symmetric EDLC cell in organic electrolyte.…”
mentioning
confidence: 99%